Penerapan Metode Debat Inisiasi dalam Membentuk Keterampilan Berbicara Siswa Kelas VIII di SMP Negeri 14 Palembang - Keysia Vectrina Zahra; Aida Imtihana; Nyimas Yunierti Prihatin (STKIP Subang, 2026)
This research was motivated by the low level of students’ speaking skills, which was indicated by a lack of confidence, low participation, and difficulties in expressing ideas during the learning process. The objectives of this research were to determine the speaking skills of students in the control and experimental classes and to examine whether there was a significant difference after the implementation of the initiation debate method. This study employed a quantitative approach using an experimental method with a Posttest-Only Control Group Design. The subjects of the study consisted of two classes, namely the experimental class and the control class, each consisting of 38 students. Data collection techniques included oral tests, observation, interviews, and documentation. The data were analyzed using validity and reliability tests, normality testing with the Kolmogorov-Smirnov test, homogeneity testing, and the Independent Sample t-Test. The results showed that the average speaking skill score of students in the experimental class was 77.10, which was higher than that of the control class at 37.89. The control class was categorized as moderate, while the experimental class was categorized as moderate to high. Based on the results of the Independent Sample t-test, the significance value (Sig. Two-Sided p) was < 0.001, indicating a significant difference between the two groups. Thus, the alternative hypothesis (Hₐ) was accepted and the null hypothesis (H₀) was rejected. Based on these findings, it can be concluded that the initiation debate method has a significant effect on developing students’ speaking skills.